MODERASI BERAGAMA DALAM QS. AL-KAFIRUUN "Analisis Hermeneutika Double Movement Fazlur Rahman" - dan Afifullah, Toyyibatul Qomariyyah Delta Yaumin Nahri (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2023)
Religious moderation is a conflict resolution over religious issues. The mention of non-Muslims as infidels is a sensitive matter because it is one of the causes of the breakdown of religious moderation. The Qur'an is always stated as a reference source that solves every problem throughout the ages. This is no exception to the problem of religious moderation. To realize the function of the Qur'an, the Qur'an needs to be understood contextually. This research is a type of literature research, namely research whose data sources are taken from various literatures. This research includes letter thematic research, namely research on certain letters in the Qur'an, in this study the focus is on QS. al-Kāfirun. The approach used is Fazlur Rahman's double movement hermeneutics because by using double movement hermeneutics it will be known how the historicity of the verse is and how it is contextualized in the present. The results of this study are that there are three principles that can be taken from QS. al-Kāfirūn in addressing religious diversity. The first is tolerance, the second is mutual respect and the third is dialogue between religious adherents. By adhering to these principles, adherents of religions will not act arbitrarily towards adherents of other religions. So that relations between humans or between religious adherents do not deny the values ​​of humanity itself. As he hoped, between humans and between religious adherents can live in harmony, peace and quiet in practicing their respective religions.